Projetar a vida sendo menina: contribuições da terapia ocupacional social - Oliveira, Maribia Taliane de (2023)
The condition of women in our society has important implications in terms of hierarchy, asymmetry, discrimination and inequality, real possibilities for the elaboration and experience of their life projects. Being a young girl, such implications are also materialized in the experience of youth, the dreams and life projects that can be built at this stage. Thus, the study aimed to identify dimensions of the lives of girls/women high school students that influence the projection of their lives, as well as the possible contributions of social occupational therapy to the construction of life projects with autonomy and emancipation. It started with the proposition of a mutual research, in the research-intervention modality, carried out in a public school that is part of the Integral Teaching program, located in a peripheral region of the city of São Carlos, from the construction of a Youth Club named "Clube das Meninas", where Workshops on Activities, Dynamics and Projects with young high school students, with themes related to the research. The meetings were recorded and registered in field diaries and then the collected data was organized, read, systematized and analyzed. The data were systematized from the grouping of the central themes discussed in each meeting of the Club, being: (a) What is it like to be a girl/woman?; (b) Daily, Invisible Work, Self-care and Pandemic; (c) Affective and/or Sexual Relationships; (d) Social Support Network; (e) Life Projects; and (f) Fanzine. Discussion: The data imply important elements related to the social conventions of gender that permeate the relationship established between girls/women, their bodies and routine, exposure to violence situations of since childhood, and when young, more significantly, in affective and/or sexual relationships, the family and friendship bonds’ weaknesses and ruptures of the absence of consistent and protective social support networks, especially, the non-recognition of the school as a component of this network and the crossing of all these elements in the construction of your life projects. Class, as a social marker of difference, linked to gender, was highlighted during the proposed discussions, showing the numerous limitations and obstacles in the field of possibilities of the girls who participated in the research, since the social relations of power related to gender and in class, produce a series of oppressions, violations and restrictions, which limit the possibilities of effective exercise of autonomy of these young girls in the projection of their lives. Therefore, we argue that social occupational therapy can contribute to facing the daily problems resulting from the social construction related to being a girl/woman and the contradictions and inequalities of a capitalist society, in the expansion of experiences with a view to autonomy and emancipation, as well as in the strengthening of social support networks and in the prevention of violence situations and fundamental elements for the construction of emancipatory life projects.